The process of transition to adulthood of young Mexicans with migration experience in the United States, 2010 - Avila Sánchez, María de Jesús; Jáuregui Díaz, José Alfredo; Granados Alcantar, José Aurelio (Universidad Autónoma de Chiapas, 2018)
This study examines the effect of the migratory experience in the United States on the transition to adulthood in five events, the first sexual relation, the first marriage or union, the first live-born child, the leaving school and first job. The National Youth Survey of 2010 (enj 2010) is used as the primary information source for its elaboration. The results show that the international migratory experience has a positive effect on the occurrence of the events of entry to the labor market, first sexual relation and leaving the school and negative in the postponement of the first marriage and the first live-born child.